1996
DOI: 10.1007/bf02247334
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of vacuous chewing movements with morphological changes in rats following 1-year treatment with haloperidol

Abstract: Long-term treatment with the typical antipsychotic drug, haloperidol, can lead to a sometimes irreversible motor disorder, tardive dyskinesia (TD). It has been hypothesized that increased release of glutamate due to prolonged neuroleptic drug treatment may result in an excitotoxic lesion in specific neuronal populations within the basal ganglia, leading to TD. We reported that treatment with haloperidol for 1 month results in an increase in the mean percentage of striatal asymmetric synapses containing a perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 47 publications
2
19
0
Order By: Relevance
“…Our results confirm and extend earlier electron microscopic studies showing that chronic haloperidol treatment produces a decrease in the density of total dendritic spines accompanied by a corresponding decrease in axo-spinous asymmetric synapses and an increase in perforated synapses (Meshul and Casey, 1989;Meshul et al, , 1996aMeshul and Tan, 1994;Roberts et al, 1995;Kelley et al, 1997). In contrast, as compared to controls, we have shown a marked increase per unit area and volume of NMDAR1-labeled spines in the dorsolateral CPN using a modified disector method.…”
Section: Increased Nmdar1 Immunoreactivity In Dendritic Spines In Thesupporting
confidence: 92%
See 2 more Smart Citations
“…Our results confirm and extend earlier electron microscopic studies showing that chronic haloperidol treatment produces a decrease in the density of total dendritic spines accompanied by a corresponding decrease in axo-spinous asymmetric synapses and an increase in perforated synapses (Meshul and Casey, 1989;Meshul et al, , 1996aMeshul and Tan, 1994;Roberts et al, 1995;Kelley et al, 1997). In contrast, as compared to controls, we have shown a marked increase per unit area and volume of NMDAR1-labeled spines in the dorsolateral CPN using a modified disector method.…”
Section: Increased Nmdar1 Immunoreactivity In Dendritic Spines In Thesupporting
confidence: 92%
“…In addition, we examined serial as well as single sections of tissue, since the numbers of labeled profiles that appear in one section are directly related to several factors, including amount and subcellular distribution of immunoreactivity, as well as shape and size of individual profiles (West, 1993;Coggeshall and Lekan, 1996). The inclusion of data from single as well as serial sections permits more direct comparisons with earlier studies of haloperidol-induced morphological changes, most of which used only single sections (Meshul et al, , 1996aMeshul and Tan, 1994;Roberts et al, 1995). The use of the disector provides additional information in all quantitative studies (Coggeshall and Lekan, 1996), but proved to be essential in the present study.…”
Section: Methodological Considerationsmentioning
confidence: 98%
See 1 more Smart Citation
“…Neuroleptic drugs may exert their effects by altering neuronal structure. Many studies show that chronic treatment of experimental animals is associated with synaptic and dendritic changes in midbrain, prefrontal, neostriatal, and accumbal neurons, changes that have been linked both to the efficacious and motor side effects of these drugs (Benes et al, 1983(Benes et al, , 1985Meredith et al, 1997;Meshul et al, 1996;Roberts et al, 1995;Vincent et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Ultrastructural studies of APD effects in the striatum primarily focus on the dorsal striatum, where chronic (6 months or longer) haloperidol treatment results in reduced asymmetric synapse density 85,86 and reduced spine number. 87 Other studies of APD treatment have reported an increased percentage of perforated synapses in the caudate with no change in total number, and no differences present in the NAcc.…”
Section: Limitationsmentioning
confidence: 99%